2020
DOI: 10.1111/jbi.13831
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic parallelism: Concordant patterns in closely related species illuminate underlying mechanisms in the historically glaciated Tasmanian landscape

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…At the same time, comparative phylogeographic approaches among closely related and ecologically similar species should be more sensitive to reflect shared processes ('phylogeographic parallelism') [110] and to point out the factors underlying discordant phylogeographic patterns, since the analysis is less biased by major biological differences of the taxa [111]. We know of no previous studies on comparative phylogeography of copepods.…”
Section: Comparative Phylogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, comparative phylogeographic approaches among closely related and ecologically similar species should be more sensitive to reflect shared processes ('phylogeographic parallelism') [110] and to point out the factors underlying discordant phylogeographic patterns, since the analysis is less biased by major biological differences of the taxa [111]. We know of no previous studies on comparative phylogeography of copepods.…”
Section: Comparative Phylogeographymentioning
confidence: 99%
“…We know of no previous studies on comparative phylogeography of copepods. But a study of two closely related species of metallic show skink in Tasmania [111] demonstrated remarkably similar phylogeographic patterns suggesting that these species responded similarly to Plio-Pleistocene climate cycling, and that glacial cold and aridity forced them into similar lowland refugial regions throughout the area. Likewise, comparison of phylogeographic patterns of 12 species from desert-dwelling fauna in the Mojave and Sonoran deserts identified six hotspots of high genetic divergence and diversity and suggested that most of the species diversified into distinct lineages prior to Pleistocene climatic changes [31].…”
Section: Comparative Phylogeographymentioning
confidence: 99%
“…We suggest that during the relatively cool conditions of the Pleistocene, the ancestral K. cognatus expanded its range to the south when the land bridge between the mainland and Tasmania was open (Lambeck and Chappell 2001) and a subsequent separation of Tasmania from the mainland led to allopatric speciation. The metallic snow skink (Carinscincus metallicus) provides a clear example of a land bridge distribution in which there are populations on the chain of Bass Strait islands between Tasmania's north-eastern cape and Victoria's Wilson's Promontory (McCoull 2000;Kreger et al 2020). We are not aware of Kosciuscola on Bass Strait islands but suggest that they could be important targets for future sampling.…”
Section: Kosciuscola Tasmanicusmentioning
confidence: 99%
“…Multispecies phylogeographic analyses of co-distributed species can provide powerful tests of ecosystem-wide evolutionary processes driven by Earth history, e.g., [5,39]. Similarly, observations of ecologically similar and closely related species increase the confidence of association between pattern and process 'phylogeographic parallelism'; sensu Kreger et al [40]. Given that drainage evolution events can cause precise spatiotemporal disruption of freshwater connectivity, multispecies phylogeography of freshwater fishes should reveal shared evolutionary histories.…”
Section: River Vicariance Synchronises Population Divergence Across Multiple Speciesmentioning
confidence: 99%